Late spring 2021 land-fast sea ice and sub-ice platelet layer thicknesses from electromagnetic induction soundings on transect TNB-2021_NS-1_EM in Gerlache Inlet, Terra Nova Bay, Antarctica - Brett, Gemma Marie; Gardiner, Natasha Blaize; Hawes, Ian; Kim, Sanghee; Rack, Wolfgang; Irvin, Anne; Langhorne, Patricia J; Haas, Christian (In: Brett, GM et al. (2025): Late spring 2021 land-fast sea ice and sub-ice platelet layer thicknesses from electromagnetic induction soundings on transects in Gerlache Inlet, Terra Nova Bay, Antarctica [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.968714, 2025)
Ground-based electromagnetic induction (EM) measurements of land-fast sea ice and sub-ice platelet layer (SIPL) thickness distributions were carried out on land-fast sea ice in Gerlache Inlet, Terra Nova Bay, Antarctica in late spring (November 3-7) of 2021. EM transects were carried out across Gerlache Inlet in north to south and east to west directions. The EM data were acquired using a frequency-domain Geonics Ltd EM31-MK2 instrument mounted on a sledge and towed by skidoo. The thicknesses of consolidated ice (sea ice plus the snow layer) and the SIPL were simultaneously retrieved from the EM31 measured response using the forward modelling and inversion methods of Irvin (2018).
Keywords: Antarctic sea ice; electromagnetic induction; ice-ocean interaction; Ice thickness; Sub-ice platelet layer